PRAWN FISHERY OF ALLEPPEY COAST DURING THE S.W. MONSOONS OF 1972-1976 - Kurup, P Surendranatha (Indian Journal of Fisheries, 2011)
the same season andalso duting the corresponding months of different seasons. The prawn catch wasmainly constituted by Metapenaeus dobsoni (Miers). June-July months weremore productive on account of recruitment of more individuals belonging tohigher size groups. The monthly average mean sizes of M. dobsoni showed greatdisparity, ranging between 75.2 mm and 91.5 mm for males and 81.3 mm and103.4 mm for females. In the species, males were found in a higher proportionthan females in lower size groups, but females occurred in higher proportionsin higher size groups. The recruitment of mature females into the fishery wasquite irregular throughout the seasons of different years under study. The analysisof stomach